Multi-purposed Ar gas cluster ion beam processing for graphene engineering. (May 2018) - Kim, Songkil; Ievlev, Anton V.; Jakowski, Jacek; Vlassiouk, Ivan V.; Sang, Xiahan; Brown, Chance; Dyck, Ondrej; Unocic, Raymond R.; Kalinin, Sergei V.; Belianinov, Alex; Sumpter, Bobby G.; Jesse, Stephen; et al.
Abstract: Graphene, with unique mechanical and electrical properties, offers diverse application opportunities from beyond Moore's nano-electronics to water filtration. However, accomplishing these relies on cleaning and processing large areas of supported and suspended graphene sheets. Here, we demonstrate the use of an Ar cluster ion beam as a versatile tool for graphene cleaning, defect engineering, and nanopore fabrication. In-situ and ex-situ characterization techniques were utilized in combination with first principles molecular dynamics, to highlight the differences in processing of the supported and suspended graphene samples. In this work, we monitor interaction of the Ar cluster ion beam with graphene as a function of ion dose with in-situ secondary ion mass spectrometry (SIMS), as well as ex-situ Raman spectroscopy measurements. Scanning transmission electron microscopy (STEM) results confirm that the Ar cluster ion beam can form nanopores in the suspended graphene; while the basal plane of graphene remains intact maintaining the lattice structure. Finally, Scanning Electron Microscopy (SEM) image analysis of the irradiated samples allows quantitative tracking of pore areas and their distribution as a function of ion dose. This study highlights the flexibility of the Ar cluster ion beam in 2D material processing, and offers insights into Ar beam interaction with graphene. Graphical abstract: Image